Le prassi applicative delle misure di tutela delle piccole minoranze trentine nelle scuole Uno Studio Interdisciplinare. Technical Report - Decarli, Giorgia (FrancoAngeli, 2022)
The report is the outcome of a research carried out in 2018 on minorities protection. The ethnographic study took place in four schools located in the areas where the Cimbrian and Mocheno linguistic communities traditionally reside. The report offers a picture both of virtuous practices that strengthen protection and of obstacles that slow down its full realization in a school that is, at the same time, a pedagogical program, a space for socialization and a place where many things happen. In line with applied anthropology, it provides institutional decisions with the support to bridge the gap between a regulatory level that requires "to do in support of minorities" and the operational level where schools factually meet minority pupils.